EVALUATION OF THE IMPLEMENTATION OF SOCIALIZATION FOR THE PREVENTION OF NON-PROCEDURAL PMI AND THE CRIME OF TRAFFICKING IN PEOPLE (DPPO) IN TAMBAKREJO VILLAGE, GURAH DISTRICT, KEDIRI REGENCY - Sania Nizar Putri Ashari; Koesmoyo Ponco Aji (Jurnal Abdimas Imigrasi, 2021)
The rise of cases of non-procedural irregular migrant workers who are treated badly while working abroad has become a problem that is constantly being discussed in the mass media. Direct socialization to the community is expected to reduce the number of cases of Non-Procedural PMI. By targeting areas that send a lot of irregular migrant workers, it is hoped that they can open their eyes to register according to procedures and not be tempted by the incitement of irresponsible and unlawful labor sending agents.